Rome and the Barbarians : the privilege of law - Soazick Kerneis (Clio@Themis)
The inheritance of Roman law is complex. On the same background created by Rome, specific legal forms grew up which resulted of the process of acculturation. In the Late Empire, there were many barbarians in the Roman carmy and military judges had to accommodate Roman rules with tribal norms The so-called barbarian laws are to be found in this military context. They were issued as a privilege, so that the bond of peoples to their own customs was strenghtened and proto-national legal aggregates settled into shape.